Awards are a Special Kind of Signal - Bruno S. Frey; Jana Gallus (Center for Research in Economics, Management and the Arts (CREMA), 2014)
Awards appear in various forms, ranging from the title "Employee of the Month" to prizes, decorations, and other honors. This contribution develops a theory designed to analyze the widely-observed phenomenon of award giving. We use signaling theory as a basis for our discussion. The perspectives of the giver, and of (potential) recipients, of awards are studied in a principal-agent framework. The analysis highlights conditions under which signaling failures are likely to arise and compares awards with monetary compensation. The paper informs management practice by presenting a systematic appraisal of the signaling functions of awards. It proposes under which conditions awards tend to raise performance, and when monetary compensation proves to be superior.
Keywords: 330; Awards; prizes; incentives; signaling theory; principal-agent framework